“Maybe being a teacher wouldn't make my mom feel proud”. Social factors involved the choice of teaching among Ecuadorian university students (Praxis Educativa, 2024)
This study aims to understand how social factors intervene in the choice of the teaching profession of Ecuadorian university students. For this purpose, a methodology with a mixed sequential explanatory approach has been used. Initially, a quantitative study was conducted to explore the sociodemographic characteristics of 362 first-year Basic Education students at two public universities through a survey. In a second moment, based on the results of the quantitative study, 6 students were selected to address their teaching professional choice through an in-depth interview. The results show that teaching is a viable vocational choice option for this group and that the presence of teachers in the family, school biography and previous experiences in education act as triggering factors for teacher choice, in a context in which there is social deterrence by some families.
Keywords: vocational choice; teaching profession; university students; social factors; family